Deeply Rooted: Maximizing the Strengths of a Historically Black University and Community‐based Participatory Research to Understand Environmental Stressors and Trauma among Black Youth. Issue 3 (12th August 2020) - Mance, GiShawn A.; Rodgers, Caryn R.R.; Roberts, Debra; Terry, Amanda
Abstract: This paper explores a partnership between an HBCU (Historically Black Colleges and Universities) and a community to understand trauma given the high rates of reported violence among youth locally. The accumulative stress of living in high‐stress, high‐poverty environments coupled with the normative developmental tasks of adolescence is thought to place these youths at risk for negative mental and physical outcomes (Murry et al., 2011). The current research uses a community‐based participatory research (CBPR) approach and developmental lens to better understand environmental stressors and subsequent trauma among Black youth. Specifically, the paper describes the recruitment, engagement, and equitable partnership between a youth advisory board (YAB), university research team, and community agencies advisory board (CAB). The current work is part of a larger research study designed to explore environmental stressors, coping, and social supports for Black youth residing in low‐resource urban communities. The broad objective of the research is to develop a trauma‐informed community intervention to improve adolescent mental health. The initial phase of this university–community research, which entails the YAB, CAB, and university discussion groups, is outlined in this paper. Community engagement and trust are key factors described in the literature when collaborating with communities of color. These themes were reiterated by research partners in this study. The research team created coding terms to identify themes from YAB and CAB transcript data, respectively. YAB themes regarding stressors centered around financial strain, anger, and loss/violence. CAB themes regarding adolescent mental health and resources centered around trauma, trust, and sustainability. Initial steps to utilize the themes identified thus far are described. The unique advantages of an HBCU and CBPR to address mental health disparities in ethnic minority communities are also highlighted. Highlights: This research uses CBPR and a developmental lens to understand stressors and trauma among Black youth. The recruitment and engagement of a youth advisory, community advisory, and university are described. Themes from discussion groups with the advisory boards are presented. The unique advantages of a HBCU and CBPR to address mental health disparities are highlighted.